Textual and Contextual Meaning Analysis in Perfume Advertisement Discourse - Wardoyo, Hadi; Jati, Muhammad Suluh (Universitas Brawijaya, 2024)
This research explores the discourse of men's perfume advertisements in Oriflame products through Guy Cook's advertisement discourse theory. The study aims to analyze the textual and contextual meaning constructions embedded within these advertising texts. Employing a qualitative critical discourse analysis approach, the research focuses on linguistic structures, visual elements, and the sociocultural context surrounding the advertisements. Cook's theoretical framework is utilized to deconstruct the dimensions of text, context, and interaction in advertising discourse. The analysis concentrates on textual aspects, including language structure, word choice, and communication style, alongside contextual elements that encompass social, cultural, and ideological backgrounds represented in the advertisements. The research investigates how masculinity, self-image, and symbolic values are constructed through strategic communication mechanisms. Findings reveal that Oriflame's perfume advertisements employ complex representational strategies in constructing contemporary masculine identity. The meaning-making process occurs through intricate interactions between verbal text, visual imagery, and dynamic social contexts, creating persuasive narratives about male identity and lifestyle. All of these aspects is made to make a perception about the true masculinity should the man have. The study contributes to understanding the sophisticated discourse mechanisms employed in contemporary marketing communication, particularly in gendered product advertising.